Transient Perivascular Inflammation of the Carotid Artery (TIPIC) Syndrome: Does Ultrasound Decipher the Myth? - R, Monga Bhagyam (Archives of Clinical and Medical Case Reports, 2019)
Transient Perivascular Inflammation of the Carotid Artery (TIPIC) syndrome; is a rare, under-diagnosed clinico-radiologic entity comprising of acute unilateral neck pain and tenderness over the affected carotid bifurcation. In patients with TIPIC syndrome or idiopathic carotidynia, diagnostic imaging demonstrates a characteristic transient perivascular soft tissue thickening at the level of the affected carotid bifurcation. This article presents a short review of literature and highlights the role of Ultrasound in the diagnosis and follow-up of patients with a presumptive diagnosis of TIPIC syndrome.